Early second‐trimester three‐dimensional transvaginal neurosonography of fetal midbrain and hindbrain: normative data and technical aspects. (3rd March 2022) - Birnbaum, R.; Barzilay, R.; Brusilov, M.; Acharya, P.; Malinger, G.; Krajden Haratz, K.
ABSTRACT: Objectives: To provide a detailed description of the sonographic appearance and development of various fetal structures of the midbrain and hindbrain (MBHB) during the early second trimester, and to evaluate the impact of the frequency of the transvaginal sonography (TVS) transducer on the early recognition of these structures. Methods: This was a retrospective analysis of three‐dimensional volumetric datasets of the MBHB from apparently normal fetuses at 14–19 gestational weeks, acquired by TVS in the midsagittal view through the posterior fontanelle. Using a multiplanar approach, we measured the tectal thickness and length, aqueductal thickness, tegmental thickness and width and height of the Blake's pouch (BP) neck. In addition, we assessed the existence of early vermian fissures, the linear shape of the brainstem and the components of the fastigium. The correlation between gestational age according to last menstrual period and sonographic measurements of MBHB structures was evaluated using Pearson's correlation ( r ). A subanalysis was performed to assess the performance of a 5–9‐MHz vs a 6–12‐MHz TVS transducer in visualizing the MBHB structures in the early second trimester. Results: Sixty brain volumes were included in the study, obtained at a mean gestational age of 16.2 weeks (range, 14.1–19.0 weeks), with a transverse cerebellar diameter range of 13.0–19.8 mm. We found a strong correlation between gestational age and all MBHB measurements, with the exception of the tectal, tegmental and aqueductal thicknesses, for which the correlation was moderate. There was good‐to‐excellent intraobserver and moderate‐to‐good interobserver correlation for most MBHB measurements. We observed that the BP neck was patent in all fetuses between 14 and 18 weeks with decreasing diameter, and that the aqueductal thickness was significantly smaller at ≥ 18 weeks compared with at < 16 weeks. The early vermian fissures and the linear shape of the brainstem were present in all fetuses from 14 weeks. We found that, in the early second trimester, the horizontal arm of the presumed 'fastigium' evolves from the fourth ventricular choroid plexus and not the posterior vermis, indicating that this is not the fastigium. Standard‐ and high‐resolution TVS transducers performed similarly in the assessment of MBHB anatomy. Conclusion: Detailed early second‐trimester assessment of the MBHB is feasible by transvaginal neurosonography and provides reference data which may help in the early detection of brain pathology involving the MBHB. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.